MANGROVE RESTORATION IN NE BRAZIL: A UNIFIED CONTRIBUTION TO ADAPTING TO GLOBAL CLIMATE CHANGE: Restauração de manguezais no NE do Brasil: uma contribuição unificadora para adaptação à mudança climática - Cesar Ferreira, Alexander; Drude de Lacerda, Luiz (Arquivos de Ciências do Mar, 2022)
The decade 2021-2030 was defined by the UN as the decade of ‘Ecosystem Restoration’ and of ‘Ocean Science for Sustainable Development’, aiming to restore ecosystems and protect the Oceans. Among target ecosystems, mangroves are fundamental wetlands, since they support a lively, biologically dynamic frontier between land and sea, furnishing many goods and services in relation to their extension, like fisheries, timber, biodiversity conservation and climate change mitigation, among others. Regarding climate change, mangrove restoration helps mitigate GHG emissions, by sequestering carbon in biomass and sediments for long periods of time and increases shore protection facing sea level rise and extreme climate events. The possibilities and conditions for mangrove restoration are many, and their rehabilitation/restoration is possible as provided by evidence form many experiments worldwide. Notwithstanding, there are still many steps in methodology and governance decisions to place mangrove restoration as a globally effective mitigation and adaptation measure to climate change. Keywords: global changes, ecosystem services, ecological rehabilitation, mitigation.